Design of immunogens to present a tumor-specific cryptic epitope - Huafeng Xu; Timothy Palpant; Qi Wang; David E. Shaw (Scientific Reports)
Abstract In many cancers, the epidermal growth factor receptor (EGFR) gene is amplified, mutated, or both. The monoclonal antibody mAb806 binds selectively to cancer cells that overexpress EGFR or express the truncated mutant EGFRvIII, but not to normal cells. This suggests that a promising avenue for developing cancer vaccines may be to design immunogens that elicit mAb806-like antibodies. In this study, we designed immunogens that present the mAb806-binding epitope in the same conformation as in overexpressed or truncated EGFR. We first used molecular dynamics simulations to identify conformations of EGFR in which the residues of the mAb806-binding epitope are accessible. We then designed immunogens by substituting that epitope in place of a structurally similar loop in a different protein and generating mutants that could potentially stabilize the mAb806-binding conformation in this new context. Two mutants in which the epitope remained stable in subsequent simulations were chosen for evaluation in vitro. Binding kinetics experiments with these designed immunogens provided strong evidence that the epitope was successfully stabilized in the mAb806-binding conformation, suggesting that they could potentially form the basis of vaccines that elicit cancer-selective antibodies.